A Photovoice Study to Reveal Community Perceptions of Highly Processed Packaged Foods in India. Issue 6 (2nd November 2021) - Srinivasapura Venkateshmurthy, Nikhil; Potubariki, Gopi; Brown, Kerry Ann; Sharma, Piyu; Ganpule-Rao, Anjali; Prabhakaran, Dorairaj; Mohan, Sailesh; Knai, Cécile
ABSTRACT: India is experiencing a nutrition transition, with sales of packaged and processed foods rapidly increasing in recent years. This study sought to understand the views and experiences of self-help groups about highly processed, packaged food in Visakhapatnam, India, using the Photovoice method. Participants were able to record, reflect on and critique their environments through participatory analysis, identifying key themes, and offering a critical lens on their food environment and experiences. On an average eight and 14 members participated in the Photovoice workshops held in urban and rural Visakhapatnam respectively. The key themes emerging from the photos and text data are that participants experienced highly processed packaged foods as being: 1) democratic (easily available and consumed by all, affordable and accessible; 2) convenient (easy to prepare) and 3) unhealthy (for human consumption and for environmental sustainability). These data demonstrate the challenges facing public health nutritionists in wishing to shift dietary behaviors to healthy habits: on the surface participants acknowledged their unhealthy characteristics, however these products may now be embedded in dietary culture. Traditional methods for changing dietary habits may not be able to capture the complexity and systems approach is required to explore the most effective entry points for affecting change.